The Poetic Revolution of (Bashar ibn Burd): A Descriptive Analytical Study - الله, ليلى عثمان عبد (Sulaimani Journal for Humanities, 2019)
Bashar bin Burd is one of the prominent Abbasid poets who is recognized as one of the innovators in the Arabic poetry and literature. His life spanned two different eras; one associated with Arabism and preservation of Arab customs and traditions. This era is marked with political and religious revolutions. He other era associated with the Persian King Khosrow who was in constant feud with the Arabs who also boasted about their new religion having occupied increasingly larger spaces. Such factors pushed the Khosrowi Persians to start antagonizing the Arabs in a different direction. They also took pride in their nationalistic icons, civilization, heritage and enormous national capital. Moreover, Bashar bin Burd was one of the most enthusiastic supporters of the Khosrawis even though he continued to win the favor of the Arab princes and kings. Bashar closely followed the conflicts taking place between the innovators and the conservatives but he tended to support the innovators more while at the same time sided with those calling for preserving the traditional literary modes. This is clear from his works where we see some of his solid poems are produced following traditional styles and some of them are molded on the newer style of his own period since he thought that art and literature are products of their own environments and times. Hence, Bashar was convinced that his poems should reflect his own time and reality resulting in a new poetic art called “the literature of the innovators”. Thus, he opened a gate for his contemporary poets and writers who followed his footsteps in innovating poetry and writing style as Bashar represented a bridge between the traditional and the modern in poetry.